Molecular identification and subtype analysis of Blastocystis in captive Asiatic black bears (Ursus thibetanus) in China’s Heilongjiang and Fujian provinces - Zhou, Yuting-Li; Zhao, Nairui; Yang, Yilei; Li, Yueqi; Zhang, Xinyu; Chen, Jiani; Peng, Xiang; Zhao, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Blastocystis sp. is the most isolated enteric protozoan in parasitological surveys of humans. A substantial percentage of human infections is attributed to zoonotic transmissions. However, the contribution of each animal source to human infections with blastocystis is not yet fully understood. This study thus aimed to determine the infection rates and subtype distributions of Blastocystis sp. in captive Asiatic black bears (Ursus thibetanus) in China’s Heilongjiang and Fujian provinces. A total of 218 fresh fecal specimens were collected from captive Asiatic black bears in Heilongjiang (n = 36) and Fujian (n = 182) between May 2015 and December 2017. Genomic DNA was extracted from each sample and then examined for Blastocystis through SSU rRNA gene amplicon-based sequencing. A phylogenetic tree based on the Blastocystis positive sequences was reconstructed using the Mega X program. Eleven percent (24/218) of the animals had Blastocystis and six Blastocystis subtypes, including ST4 (n = 14), ST10 (n = 3), ST1 (n = 2), ST2 (n = 1), ST5 (n = 1), and ST12 (n = 1) were identified. A total of 14 representative sequences, including seven sequences that have been described previously and seven novel sequences comprising ST10 (n = 2), ST5 (n = 1), and ST4 (n = 4), were obtained from the six subtypes of Blastocystis. This study is the first to report the presence of Blastocystis in captive Asiatic black bears in Fujian, China. It provides baseline data for controlling and preventing Blastocystis infection in farm communities. Zoonotic infections in bears with ST1, ST2, ST4, ST5, ST10, and ST14 should be considered potential public health threats. The novel ST sequences of Blastocystis generated in this study provide novel insights into the genotypic variation within the Blastocystis sp.